Eco-physiological evaluation of provenances of Schizolobium parahyba subsp. amazonicum in the moltingstage and its growth in the field (Research, Society and Development, 2021)
Seed provenances are important for the establishment of forest plantations. The objective of the study was to evaluate subspiation in echo-physiological characters of provenances of S. parahyba subesp. amazonicum (Huber ex Ducke) Barneby in the nursery stage and its initial growth in the field. In the nursery stage, the photosynthesis rate, transpiration, stomatal conductance, stem height and diameter, and dry matter distribution were evaluated; In the field stage, the survival of the plants and their growth in height and diameter were evaluated two years after sowing. The provenances Ji-Paraná (RO), Belterra (PA), Alta floresta (MT) and Brasiléia (AC) were used. . A completely randomized experimental design was used in the nursery and a randomized complete block design with three repetitions in the field. The parameters photosynthesis, stomatal conductance and transpiration in the nursery phase showed significant subspiation between provenances (p≤ 0.05), where the Brasiléia provenance presented a higher rate of stomatal conductance and transpiration, while Alta forest had higher values ​​of photosynthesis. The Ji-Paraná and Alta Floresta provenances, in the nursery phase, because they presented a higher allocation of trunk biomass (56.9%) and root (52.2%) respectively, showed greater potential for use in forestry so that it will be able to promote better performance of plants under field conditions.